Aplikasi Layanan Pengangkutan Sampah Berbasis Android - Kai, Harry N.; Sompie, Sherwin R.U.A.; Sambul, Alwin M. (Universitas Sam Ratulangi, 2018)
Abstract — Definition of waste is something that is unwanted or unwanted by having and being solid. In the city of Manado, the application of the garbage transportation system is still manual, where people in Manado city must bring the garbage that has been collected to the TPS (Temporary Disposal) or only placed near the house. This is a problem where there is often a neglect of the transportation of garbage in polling stations or in people's homes, this makes the waste more and more mountainous, this is a view that reduces the aesthetic value of smart city carried by the Manado City government. An Android-based Garbage Transport Service Application is designed to support the community to participate in the waste transportation process and also maximize the use of existing garbage transport services. This application was made with the aim of overcoming the problem in the garbage transport system which shows irregularity, neglect, neglect and inefficiency in the use of garbage transportation from any polling station or random place to landfill using the RAD method in making a system development cycle that has three types of stages, namely planning requirements requirements, RAD design workshops and implementations and using IDE Android Studio to create object-oriented programming systems using Java. The results of the design and construction of the Android-based Garbage Transport Service Application are to be used by residents who act as users and drivers, namely as parties who will carry out garbage transport activities that previously only used manual methods in the process of preparing ready-to-carry garbage and transportation by garbage providers transportation Keywords - Garbage Transportation, RAD, Users, Services Abstrak — Pengertian sampah adalah sesuatu yang tidak dikehendaki atau tidak diinginkan lagi oleh yang memiliki dan bersifat padat. Di kota Manado, penerapan sistem pengangkutan sampah masih bersifat manual, dimana masyarakat di kota Manado harus membawa sampah yang sudah dikumpulkan ke TPS (Tempat Pembuangan Sementara) atau hanya diletakkan di dekat rumah. Ini menjadi masalah dimana sering terjadinya pengabaian terhadap pengangkutan sampah di TPS ataupun di rumah-rumah warga, hal ini membuat sampah tersebut makin banyak dan menggunung, ini merupakan suatu pemandangan yang mengurangi nilai estetika smart city yang diusung oleh pemerintah Kota Manado. Dirancanglah sebuah Aplikasi Layanan Pengangkutan Sampah Berbasis Android untuk mendukung masyarakat berpartisipasi dalam proses pengangkutan sampah dan juga memaksimalkan penggunaan layanan angkut sampah yang ada. Aplikasi ini dibuat dengan tujuan untuk mengatasi masalah pada sistem pengangkutan sampah yang menunjukkan adanya ketidakteraturan, pengabaian, melalaikan dan tidak efisiensinya penggunaan angkutan sampah dari TPS atau tempat sembarang menuju TPA dengan menggunakan metode RAD dalam membuat siklus pengembangan sistem yang memiliki tiga macam tahap yaitu perencanaan syarat-syarat, workshop desain RAD dan implementasi serta menggunakan IDE Android Studio pembuatan sistem berbasis pemrograman berorientasi objek menggunakan Java. Hasil dari perancangan dan pembangunan Aplikasi Layanan Pengangkutan Sampah Berbasis Android adalah untuk digunakan oleh warga yang berperan sebagai user dan driver yaitu sebagai pihak yang akan melaksanakan kegiatan angkut sampah yang sebelumnya hanya menggunakan cara manual dalam proses menyiapkan sampah siap angkut dan pengangkutan sampah oleh pihak penyedia layanan pengangkutan. Kata kunci — Angkutan Sampah, RAD, User, Layanan